2010
DOI: 10.1111/j.1728-4457.2010.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐Household Conflicts in Migration Decisionmaking: Return and Pendulum Migration in Morocco

Abstract: By analyzing the migration behavior and transnational residential strategies of first-generation, aging migrants from a particular Moroccan sending region, this study contributes to a conceptual critique of migration theories that identify the household as the most relevant decisionmaking unit. It highlights the role of intra-household power inequalities and conflicts in migration decisionmaking as well as the effects of migration decisions for intra-household power relations. Many labor migrants who left Moro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 20 publications
1
83
0
3
Order By: Relevance
“…De Haas and Fokkema (2010) found, similarly, that sons of Moroccan return migrants tend to resent their fathers' decision to return since it blocks their own chances of gaining admission to Europe.…”
Section: Losing Dutch Citizenshipmentioning
confidence: 86%
See 1 more Smart Citation
“…De Haas and Fokkema (2010) found, similarly, that sons of Moroccan return migrants tend to resent their fathers' decision to return since it blocks their own chances of gaining admission to Europe.…”
Section: Losing Dutch Citizenshipmentioning
confidence: 86%
“…Although retirement migration in general is increasingly studied, the experiences of post-retirement returnees are still largely under-researched, especially from a gender lens (exceptions include Ackers and Dwyer, 2002;Balkır and Böcker, 2015;Bolzman et al, 2006;De Coulon and Wolff, 2010;De Haas and Fokkema, 2010;Hunter, 2011;Krumme, 2004). Earlier studies on return migration to the Mediterranean region have focussed mainly on the return of working-age migrants and do not incorporate the experiences of post-retirement returnees in their analysis.…”
Section: Gender and (Retirement Return) Migrationmentioning
confidence: 99%
“…The qualitative study of De Haas and Fokkema (2010) on older Moroccan pendular and return migrants is an excellent example in showing that the two migrant groups differ mainly with respect to the location of their family members: while pendular migrants generally brought over their wives and children in the 1970s and 1980s, most return migrants decided to leave their family in the country of origin. Several quantitative studies have also shown that, besides economic ties (e.g.…”
Section: After Living In Italy For Thirty Years It Would Be a Radicamentioning
confidence: 99%
“…Key reasons to stay include living close to children and grandchildren, retaining pension rights and residence permits, and having access to good quality of healthcare services and social security (Bolzman et al, 2006;De Haas & Fokkema, 2010;Ganga, 2006;White, 2006). Making the decision to maintain official residence in Europe does not mean, however, that older migrants cut or loosen the ties with their country of origin.…”
mentioning
confidence: 99%
See 1 more Smart Citation